2021
DOI: 10.21608/ejchem.2021.96445.4513
|View full text |Cite
|
Sign up to set email alerts
|

Diamide Insecticides: Efficacy, Toxicity and Analytical Methods for Residue Monitoring in Food Samples

Abstract: Anthranilic diamide is a new commercial group of insecticides that target insect ryanodine receptors, causing uncontrolled calcium ion release and depletion, which prevents muscular contraction. Due to the high advantages of diamide over other insecticide groups, it has been applied to control a variety of insect pests on a wide range of agricultural crops. The development of this group has encouraged agricultural producers to increase their reliance on it to protect crops from pest damage, resulting in increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Chlorantraniliprole is one of the insecticides detected one time only in apple. This insecticide is one of the diamide insecticides that are widely used against a variety of insect pests due to their selectivity and low mammalian toxicity [39][40][41]. Tian et al [42] determined diamide insecticides in mushrooms and found that these insecticides can be effectively analyzed using HPLC-MS/MS with LOD and LOQ of 0.05 and 5 ug kg −1 , respectively, and recovery rates ranging from 73.5-110.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorantraniliprole is one of the insecticides detected one time only in apple. This insecticide is one of the diamide insecticides that are widely used against a variety of insect pests due to their selectivity and low mammalian toxicity [39][40][41]. Tian et al [42] determined diamide insecticides in mushrooms and found that these insecticides can be effectively analyzed using HPLC-MS/MS with LOD and LOQ of 0.05 and 5 ug kg −1 , respectively, and recovery rates ranging from 73.5-110.2%.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that only 0.1% of applied chemical pesticides are effectively used for preventing, controlling, and mitigating pests, while the rest remains in the soil [14] causing toxicity to the biota and thereby entering into the food chain. Therefore, the contamination of fruits, vegetables, and other field crops possess a serious health risk to the public [15][16][17]. The impact of pesticide contamination on food has been well studied in North America, Japan, and many parts of Europe.…”
Section: Introductionmentioning
confidence: 99%